USE OF 177Lu-PSMA FOR RADIONUCLIDE THERAPY IN PATIENTS WITH CASTRATE-RESISTANT PROSTATE CANCER - A. A. Medvedeva; V. I. Chernov; E. A. Usynin; R. V. Zelchan; O. D. Bragina; N. A. Lushnikova (Сибирский онкологический журнал)
Purpose of the study: to present current data regarding challenges in treatment of castration-resistant prostate cancer (CRPC) and the relationship between CRPC and the expression of prostate-specific membrane antigen (psma).Material and Methods. The search for relevant sources was carried out in the Pubmed, elibrary, Medline databases. The review included 43 publications, most of which were published over the past 5 years.Results. Currently, prostate cancer (PC) is one of the most common cancers in men. Moreover, over time, most patients develop resistance to therapy, which significantly worsens the prognosis of the disease. Psma is one of the molecular markers of prostate cancer; a number of studies have demonstrated a direct correlation between the level of psma expression and the tumor grade, stage and aggressiveness. Numerous studies indicate that psma represents an excellent target for radionuclide therapy of prostate cancer. 68Ga or 18F-psma Pet/Ct is the most common method for diagnosing PC. It should be noted that modern trends in the development of nuclear medicine are closely related to theranostics; therefore, the creation of highly specific theranostic pairs for diagnosis and subsequent therapy of malignant tumors is of great significance. The data obtained indicate that 177lu demonstrates the most optimal radiation and physical characteristics for therapeutic radionuclides, while psma-617 is one of the most studied ligands for radionuclide therapy.Conclusion. Currently, there are several studies covering radionuclide therapy with various psmacompounds labeled with 177lu. Radionuclide therapy with 177lu-psma has been shown to be recommended for patients with metastatic CRPC, who have no benefits from alternative therapies or have contraindications to them.